Adaptive Learning in the Independent Curriculum: Integration of Behavioristic, Cognitive and Constructivist Theories in Educational Technology - Darmawati A; Marwan, Marwan; Suhenrik P; Rizal Arizaldy Ramly; Supardi Salam (International Journal of Education, Vocational and Social Science, 2023)
Education is one of the important pillars in shaping the future of the nation. Rapid changes in a world filled with uncertainty and destruction prompted governments to evaluate and update educational curricula. In Indonesia, this effort is carried out through the Merdeka Curriculum which covers education levels ranging from elementary to tertiary education. In an effort to respond to the challenges of a changing world, this curriculum is integrated with diverse educational theories, such as behavioristic, cognitive, and constructivist theories, according to the level of education and the field of educational technology. An approach that aligns education with the challenges of a changing world. The integration of behavioristic, cognitive, and constructivist theories according to the level of education and the field of educational technology is the key to its success. With this approach, it is expected that graduates can face uncertainty and destruction with strong skills, knowledge, and understanding.